Splitting Tensile Strength of Lightweight Foamed Concrete with Polypropylene Fiber - Raupit, Freccy; Saggaff, Anis; Tan, Cher Siang; Lee, Yee Ling; Md Tahir, Mahmood (International Journal on Advanced Science, Engineering and Information Technology, 2017)
This paper presents the design mix of foamed concrete and split tensile strength of lightweight foamed concrete with the addition of polypropylene fiber. The design mix of the foamed concrete was targeted to achieve a density of 1500 kg/m3. Six different water-cement ratios (w/c) range from 0.30 to 0.40 were taken into consideration. Three different group of LFC with 0% PP, 0.25% PP and 0.40% PP are prepared. The optimum w/c was determined by comparing the compressive test result of different percentage polypropylene fiber. By using the LFC with optimum w/c ratio and designated amount of PP of 3:1 c/s ratios, the concrete specimens were tested with splitting tensile test to determine the effects of PP to the tensile strength of the lightweight foamed concrete. From the result, it is found that by using 2:1 c/s ratio, the optimum w/c of mix with 0% PP, 0.25% PP and 0.40% PP are 0.36, 0.34 and 0.32 respectively, while for c/s equals to 3:1, the optimum w/c are 0.34, 0.32 and 0.32 respectively. From the splitting tensile result, under a controlled density of 1500 ± 50 kg/m3, the tensile strength range of 0.991-2.138 MPa were observed. From the result, it can be concluded that, the addition of polypropylene fiber to the lightweight foamed concrete does affect the tensile strength of the foamed concrete. However further addition of PP will not cause any positive and significant effect to the tensile strength of lightweight foamed concrete.